Pendugaan daya gabung bobot biji jagung dalam persilangan Diallel Lengkap Lima tetua = Combining Ability Estimates for Corn Grain Weight of Five - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
An attempt to estimate general combining ability (GCA), specific combining ability (SCA), and extranuclear effect of corn grain weight of five varieties using modified complete diallel cross was done to elaborate genetic components controlling the expression of the trait. The modification considered triploid nature of the endosperm, tissue that most responsible in determining grain characteristics.The estimates would qualify which parent(s) or cross combination(s) to be selected. The analysis of variance revealed that GCA and extranuclear effects played important role in determining corn grain weight. In genetical sense, additive nuclear gene action, cytoplasmic genes and maternal contribution must be considered. 'Vanarasi 9349', 'S97 TEW GH 'A y B' (3)', and 'La Galigo' varieties were potential as pollen source to raise grain weight, whereas 'Vanarasi 9349' could be chosen as female stock due to its positive and significant extranuclear effect.